2017
DOI: 10.1111/jse.12265
|View full text |Cite
|
Sign up to set email alerts
|

The Compositae Tree of Life in the age of phylogenomics

Abstract: Comprising more than 25 000 species, the Sunflower Family (Compositae or Asteraceae) is the largest family of flowering plants. Many of its lineages have experienced recent and rapid radiations, and the family has a deep and widespread history of large-scale gene duplications and polyploidy. Many of the most important evolutionary questions about the family's diversity remain unanswered due to poor resolution and lack of support for major nodes of the phylogeny. Our group has employed a phylogenomics approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 33 publications
1
65
0
1
Order By: Relevance
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the cosmopolitan family Asteraceae comprises between 1600 and 1700 genera and 25 000 species (Mandel et al, ). The group originated in South America a least 70–50 mya and then experienced several spectacular radiations.…”
Section: Introductionmentioning
confidence: 99%
“…Within Solanaceae, the genus Solanum L. is the largest and includes 1400 species (Knapp, 2013 Lamiaceae has 7200 species in 236 genera (Drew et al, 2017) which are classified in twelve subfamilies (Li et al, 2016;Li & Olmstead, 2017). Subfamily Nepetoideae includes 3660 species, 105 genera and three tribes (Drew & Sytsma, 2012 Lastly, the cosmopolitan family Asteraceae comprises between 1600 and 1700 genera and 25 000 species (Mandel et al, 2017). The group originated in South America a least 70-50 mya and then experienced several spectacular radiations.…”
mentioning
confidence: 99%
“…Liabeae are a phylogenetically derived small tribe within the Compositae (Panero & al., ; Mandel & al., , ) with 21 genera and 165 species (Gutiérrez, ; Funk & al., ; Gutiérrez & Katinas, ). This Neotropical tribe is distributed mainly in the Andes where its origin was postulated, especially in the Central and northern Andes (Funk & al., , ; Dillon & al., ).…”
Section: Introductionmentioning
confidence: 99%